The Superior Colliculus and Amygdala Support Evaluation of Face Trait in Blindsight - Ajina, Sara; Pollard, Miriam; Bridge, Holly (Frontiers in Neurology, 2020)
Humans can respond rapidly to viewed expressions of fear, even in the absence of conscious awareness. This is demonstrated using visual masking paradigms in healthy individuals, and in patients with cortical blindness due to damage to the primary visual cortex (V1) - so called affective blindsight. Humans have also been shown to implicitly process facial expressions representing important social dimensions. Two major axes, dominance and trustworthiness, are proposed to characterize the social dimensions of face evaluation. The processing of both types of implicit stimuli is believed to occur via similar subcortical pathways involving the amygdala. However, we do not know whether unconscious processing of more subtle expressions of facial trait can occur in blindsight, and if so how. To test this, we studied thirteen patients with unilateral V1 damage and visual field loss. We assessed their ability to detect and discriminate faces that had been manipulated along two orthogonal axes of trustworthiness and dominance to generate five trait levels: dominant, submissive, trustworthy, untrustworthy, and neutral, inside the blind visual field. We compared neural activity and functional connectivity in patients classified as blindsight positive or negative for these stimuli. We found that dominant faces were most likely to be detected above chance, with individuals demonstrating unique interactions between performance and face trait. Only patients with blindsight (n=8) showed significant preference in the superior colliculus and amygdala for face trait in the blind visual field, and a critical functional connection between the amygdala and superior colliculus in the damaged hemisphere. We also found a significant correlation between behavioural performance and fMRI activity in the amygdala and lateral geniculate nucleus, across all participants. Our findings confirm that affective blindsight involving the superior colliculus and amygdala extends to the processing of socially salient but emotionally neutral facial expressions when V1 is damaged. This pathway is distinct from that supporting motion blindsight, as both types of blindsight can exist in the absence of the other with corresponding patterns of residual connectivity.